Identification model of 12 year-old boys’ badminton talents - Purnama, Sapta Kunta; Hidayatullah, Muhammad Furqon; Doewes, Rumi Iqbal (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Talent identification of in badminton was needed as a prediction of the future performance of young players who will achieve success at the national or international level in badminton. The aim of the study was to establish a model for identifying badminton talent in 12-year-old boys. An observational design was used. The sample included 29 boys aged 12 years with no prior badminton experience and 29 boys who were members of a badminton club. All participants completed eight anthropometric tests and 16 physical fitness tests. The differences results between two groups were used as criteria for 12-year-old boys’ badminton talent. To determine the best talent predictor, a stepwise discriminant analysis was performed. Based on stepwise discriminant analysis, 11 measurements (four anthropometric and seven physical fitness) were identified that maximally discriminate between talented and non-talented badminton players. Using Fisher’s linear discriminant functions based on these 11 measures, 98.3% of participants were correctly classified, indicating high validity. The distinguishing characteristics between talented and non-talented players included BMI, total skinfold thickness, arm circumference, arm length, upper limb muscle power, speed, side-to-side agility, 4-corner agility, VO₂max, wrist flexibility, and eye–hand coordination. Among these, four anthropometric tests and six physical fitness tests were particularly effective in differentiating between talented and non-talented players.